Champions of the Cherokees : Evan and John B. Jones - McLoughlin, William G. (William Gerald), 1922-1992 (Princeton legacy library, 1990)
Champions of the Cherokees is the story of two extraordinary Northern Baptist missionaries, father and son, who lived with the Cherokee Indians from 1821 to 1876. Told largely in the words of these outspoken and compassionate men, this is also a narrative of the Cherokees' sufferings at the hands of the United States government and white frontier dwellers. In addition, it is an analysis of the complexity of interracial relations in the United States, for the Cherokees adopted the white man's custom of black chattel slavery. This fascinating biography reveals the unusual extent to which Evan and John B. Jones challenged prevailing federal Indian policies: unlike most other missionaries, they supported the Indians' right to retain their own identity and national autonomy. William McLoughlin vividly describes the "trail of tears" over which the Cherokees and Evan Jones traveled eight hundred miles through the dead of winter--from Georgia, Alabama, Tennessee, and North Carolina to a new home in Oklahoma. He examines the difficulties that Jones encountered when, alone among all the missionaries, he expelled Cherokee slaveholders from his mission churches. This book depicts the Joneses' experiences during the Civil War, including their chaplaincy of two Cherokee regiments who fought with the Northern side. Finally, McLoughlin tells how these "champions of the Cherokees" were adopted into the Cherokee nation and helped them fight detribalization. Originally published in 1990. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905